Pengaruh Ukuran Perusahaan Dan Umur Perusahaan Terhadap Return On Asset Pada Perusahaan Manufaktur Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2018-2020 - Asti Rahmatika Innaya; ruslinda agustina; Mellani Yuliastina; Soedjatmiko Soedjatmiko (Universitas Muhammadiyah Bengkulu, 2022)
ABSTRACT The purpose of this study was to determine the effect of firm size and age on return on assets in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. The research method is quantitative research. The population in this study amounted to 15 companies. The sample in this study was 45 companies using a purposive sampling technique. The data analysis technique used multiple linear regression processed with the SPSS version 26 program. The results showed that firm size had no effect on Return on Assets with a significance of 0.506 (0.506 > 0.05), firm age had an effect on Return on Assets with a significance of 0.002 (0.002 < 0.05), and the size and age of the company simultaneously have an effect